Profile and Clinical Outcome of Children with Wilms' Tumor treated at a Tertiary Care Centre, India - Pritanjali Singh; Dharmendra Singh; Bindey Kumar; Prem Kumar; Punam Prasad Bhadani (South Asian Journal of Cancer, 2022)
Abstract